Thermophoretic immunoassay based on autodisplayed Z-domains for the diagnosis of C-reactive protein - Lee, Ga-Yeon; Park, Min; Kang, Min-Jung; Langer, Klaus; Jose, Joachim; Pyun, Jae-Chul (ELSEVIER SCIENCE SA, 2018)
Immunoassays are used to detect a target analyte by using specific interaction with detection antibodies which form antigen-antibody complexes. In thermophoretic immunoassays the antigen-antibody complexes make slow thermophoresis (movement by thermal stimulation) in comparison with unbound antigens and antibodies. In this work, a sensitive thermophoretic immunoassay was demonstrated by mixing outer membrane (OM) particles of E. coli with autodisplayed Z-domains. In order to compare the influence of OM particles with autodisplayed Z-domains on the sensitivity of thermophoretic immunoassay, the conventional method only with target analyte and detection antibodies was compared with the hyper sensitive thermophoretic immunoassay by mixing OM particles with autodisplayed Z-domains, and the affinity constant was calculated. Finally, the diagnosis of inflammation by detection of a biomarker called C-reactive protein (CRP) was carried out by demonstrating the thermophoretic immunoassay for CRP based on autodisplayedZ-domains could be applied for the medical diagnosis. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ESCHERICHIA-COLI; OUTER-MEMBRANE; E. COLI; SURFACE DISPLAY; BIOSENSOR; IMMOBILIZATION; SYSTEM